Optimasi Pengolahan Minuman Sereal Instan Berbasis Tepung Pisang Jantan (Musa Acuminata Colla) dan Tepung Sorgum (Sorghum Spp) - Hesti Nur'aini; Femmi Muharsyaida; Lina Widawati (Sci-tech Journal, 2026)
Instant cereal is an alternative food to replace staple foods, especially for breakfast that is rich in nutrition. A study has been conducted that aims to characterize the effect of the composition of banana flour and sorghum flour on the quality of instant cereal drinks. This study used a one-factor factorial design, namely the ratio of banana flour and sorghum flour with six treatment levels, namely P1K1 (0%:100%), P2K2 (20%:80%), P3K3 (40%:60%), P4K4 (60%:40%) and P5K5 (80%:20%), P6K6 (100%:0%). Physical analysis conducted on instant cereal drinks resulted in a yield of 94.70% to 94.70%, an absorption capacity of 1.20% to 1.50%, a viscosity of 49.15 mPa.s to 89.71 mPa.s, and a humidity of 1.69% to 3.24%. Chemical analysis yielded a moisture content of 1.55% to 2.61%, a protein content of 3.30% to 6.27%, and a fiber content of 2.04% to 3.05%. The best treatment analysis for appearance parameters yielded a value of 0.87 and an effectiveness value of 1.00. The feasibility analysis yielded a R/C ratio of 1.20.